Short-Form 36, Escala de Autoestima Rosenberg-UNIFESP/EPM e Oral Health Impact Profile em pacientes submetidos ao clareamento dental - Brankovic, Milene Russo [UNIFESP] (2010)
INTRODUCTION: Technological advances in dental bleaching have allowed success in dental treatment, with greater effectiveness in indirect benefits such as awareness of oral hygiene, changes in habits and preservation of functional capacity as also well-being and longevity with consequent oral health, which considers the quality of life and self-esteem. OBJECTIVE: To evaluate the quality of life and self-esteem in patients undergoing tooth whitening. METHODS: Forty-five patients (30 patients in study group and 15 in control group) were submitted to dental bleaching and to self-applied questionnaires to assess self-esteem, quality of life and oral health (Rosenberg, SF-36 and OHIP-49). RESULTS: Through the nonparametric Wilcoxon test statistically significant differences were observed in self-esteem of study group (p=0,002), as well as the SF-36 vitality domain (p=0,019). In the OHIP- there was no significant difference in functional limitation domain (p-0.015); physical pain (p-0,014); psychological distress (p=0,003) and psychological disability (p=0,016). In the nonparametric Mann-Whitney test, intergroup analysis showed difference of statistical significance in self-esteem (p=0,011), as also in the OHIP-49 in psychological discomfort (p=0,045), psychological disability (p=0,017) and total domains (p=0,040). The SF3-6 showed no significant difference in any questionnaire. CONCLUSION: Tooth whitening presented a positive impact on selfesteem and quality of life of patients.